The role of thyrostimulin and its potential clinical significance - Karponis Dimitrios (Sciendo, 2017)
Thyrostimulin is a glycoprotein heterodimer of GPA2 and GPB5, first described in 2002. It is involved in the physiological function of several tissues. Moreover, evidence points towards the ability of thyrostimulin’s individual monomers to induce a biological effect, which could denote the circulatory/systemic effects of the molecule when found in higher concentrations. From the evolutionary point of view, thyrostimulin shares a binding epitope with the thyroid-stimulating hormone for the thyroid stimulating hormone receptor, whilst possessing affinity for another unique binding site on the same receptor. Although thyrostimulin can be involved in the hypothalamicpituitary- thyroid axis, its presence in various tissues in an eclectic array of different species renders it multifunctional. From weight loss via increasing metabolic rate to progression of cancer in human ovaries, it is certainly not a signaling molecule to overlook. Furthermore, thyrostimulin has been implicated in bone metabolism, acute illness, and reproductive function. In summary, to our knowledge, this is the first review dealing with the physiological role of thyrostimulin and its potential applications in the clinical practice.